The identification of autoantigens in mucous membrane pemphigoid using immortalized oral mucosal keratinocytes. (24th October 2018) - Kamaguchi, Mayumi; Iwata, Hiroaki; Miyauchi, Toshinari; Ujiie, Hideyuki; Ujiie, Inkin; Nomura, Toshifumi; Ohga, Noritaka; Shimizu, Hiroshi; Kitagawa, Yoshimasa
Abstract : Background: Mucous membrane pemphigoid (MMP) is a rare chronic autoimmune subepithelial blistering disorder, targeting multiple basement membrane zone (BMZ) proteins including collagen XVII (COL17). Circulating autoantibodies of MMP are often undetected due to their lower titers. The oral mucosa is a valuable substrate for the detection of autoantibodies in MMP patients. However, obtaining normal human oral mucosa is more difficult than obtaining normal human skin. We established immortalized normal human oral mucosal keratinocytes (OMKs) and performed immunoblotting using immortalized OMK lysate for detecting autoantigens in MMP. Methods: Immortalized OMKs were generated from primary OMKs using E6/E7 proteins of HPV. We compared the protein expression levels of major BMZ proteins between primary OMKs and immortalized OMKs. We performed immunoblotting to detect autoantigens using cell lysates from immortalized OMKs in 30 MMP patients. Results: There were no significant differences between primary OMKs and immortalized OMKs in terms of protein expression levels of the BMZ proteins, including COL17, laminin 332, integrin α6/β4, collagen VII, and collagen IV. Cell lysates of immortalized OMKs effectively identified MMP autoantigens in 60% (18/30) of MMP sera. We found an interesting case of MMP whose autoantibodies preferentially reacted to the 120‐kD protein that is an ectodomain of COL17. Conclusion: We demonstrated that a cell lysate of immortalized OMKs is a reliable substrate for the detection of MMP autoantigens. This newly developed immunoblotting analysis method promises to contribute to the diagnosis of MMP.